Health Behaviors Among High School Girls - Minoo Motaghi; Mansoureh Afsar (Shiraz University of Medical Sciences, 2015)
Background: Improving health-related behaviors maintain function and independence and improve the quality of life and reduce health care costs. The characteristics of puberty in girls, their physical and mental conditions during this period, and also their essential role in fertility underline the great importance of health care in adolescent girls. Objectives: The aim of this study is to determine the health-promoting behaviors in high school students in district 2 of Isfahan. Patients and Methods: This descriptive study was conducted on 500 high school girl students selected by multi-stage random sampling in district 2 of Isfahan. The data collection was based on standard questionnaire of health promoting behaviors (HPLPII), filled by the participants which was analyzed using descriptive and inferential statistics by SPSS win/11. Results: The findings of this study indicated that the total mean score of health promoting behaviors in students was 71.2 ± 21. The highest score gained by the studied population was related to the spiritual growth (19.7 ± 6.1) and the lowest score to physical activity (6.1 ± 4.7). Conclusions: Considering adolescence period as a foundation for the future life and society's health, providing appropriate hygienic, consultation and educational services to adolescents and their families should be emphasized and included in the hygienic schedules of schools.